Analisis swot: strategi pengembangan perbankan syariah dalam ekonomi global - Salsabila, Nisrina (Maliki Interdisciplinary Journal, 2025)
Islamic banking has experienced rapid growth since its emergence in the 1970s as an alternative to the conventional interest-based banking system. This development has been driven by the need for financial transactions that comply with Sharia principles and the growing interest in more ethical financial systems. In Indonesia, Islamic banking began to develop with the establishment of Bank Muamalat in 1992. This study discusses the development of Islamic banking in Indonesia, its key role in economic stability, financial inclusion, and infrastructure financing, as well as the challenges it faces, such as the lack of standardization and competition with conventional banks. Through a SWOT analysis, this study identifies the strengths of Islamic banking, such as its profit-sharing business model, as well as the opportunities that have emerged in the era of fintech and sustainable investment. The study adopts a literature review approach to provide a comprehensive overview of the position and prospects of Islamic banking in the global economy.